Quiet Activism Climate Action at the Local Scale - Steele, Wendy; Hillier, Jean; MacCallum, Diana; Byrne, Jason; Houston, Donna (Springer International Publishing : Imprint: Palgrave Macmillan, 2021)
XIV, 166 p. 21 illus.